2020
DOI: 10.1177/1971400920977206
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-induced acute kidney injury in acute ischaemic stroke patients

Abstract: Purpose The potential nephrotoxicity of intravenous iodinated contrast media is a major concern for acute ischaemic stroke imaging evaluation. This study aimed to assess the incidence of acute kidney injury after intravenous iodinated contrast media exposure in acute ischaemic stroke patients. Methods We conducted a retrospective cohort analysis between January 2012 and July 2018 to select adult patients admitted to the emergency department with acute ischaemic stroke. The exposed patients received a uniform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Overall, the definition used impacted the CIN incidence reported, but reasons for choosing a particular definition were not mentioned in most studies (n = 12). Only six studies justified their definition by stating that it was a common criterion used in various literatures [ 13 , 20 , 21 , 26 , 27 , 28 ]. Hence, the definitions will be further discussed in terms of the sCr measurements and the post-CECT sCr collection time used.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, the definition used impacted the CIN incidence reported, but reasons for choosing a particular definition were not mentioned in most studies (n = 12). Only six studies justified their definition by stating that it was a common criterion used in various literatures [ 13 , 20 , 21 , 26 , 27 , 28 ]. Hence, the definitions will be further discussed in terms of the sCr measurements and the post-CECT sCr collection time used.…”
Section: Resultsmentioning
confidence: 99%
“…An absolute sCr increase of ≥0.3 mg/dL or ≥1.5-fold increase over baseline sCr was also used to define CIN in three different studies and they reported varying incidence of 6.2% [ 21 ], 7.2% [ 23 ], and 13.2% [ 20 ]. Hence, besides factors such as sample size, CT scan region, and patient characteristics, the sCr value and range utilized in the definition of CIN is critical and could have contributed to the wide variation in CIN incidence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations